2016
DOI: 10.1186/s12893-016-0132-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting number of lymph nodes harvested and the impact of examining a minimum of 12 lymph nodes in stage I-III colorectal cancer patients: a retrospective single institution cohort study of 1167 consecutive patients

Abstract: BackgroundTo identify factors affecting the harvest of lymph nodes (LNs) and to investigate the association between examining a minimum of 12 LNs and clinical outcomes in stage I-III colorectal cancer (CRC) patients.MethodsThe clinicopathologic features and the number of examined LNs for 1167 stage I-III CRC patients were analyzed to identify factors affecting the number of LNs harvested and the correlations between clinical outcomes and high harvests (≧12 LNs) and low harvests (<12 LNs).ResultsA multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 31 publications
3
54
1
Order By: Relevance
“…Tsai et al analyzed 1,167 stage I-III CRC patients and categorized high harvests ( ≧ 12 lymph nodes) and low harvests (< 12 lymph nodes). They found that patients with low harvests had poorer OS with stages II and III CRC (stage II: p < 0.0001; stage III: p = 0.001) [31]. In the present study, similar results were obtained, and multivariate analysis showed that the number of lymph nodes was a significantly independent factor for both OS and DFS.…”
Section: Discussionsupporting
confidence: 86%
“…Tsai et al analyzed 1,167 stage I-III CRC patients and categorized high harvests ( ≧ 12 lymph nodes) and low harvests (< 12 lymph nodes). They found that patients with low harvests had poorer OS with stages II and III CRC (stage II: p < 0.0001; stage III: p = 0.001) [31]. In the present study, similar results were obtained, and multivariate analysis showed that the number of lymph nodes was a significantly independent factor for both OS and DFS.…”
Section: Discussionsupporting
confidence: 86%
“…LNY is an important prognostic factor in patients with stage II–III colorectal cancer, but evidence for stage I colorectal cancer is unclear,,. Although there are studies reporting differences in survival between low and high LNY in patients with Dukes' A/stage I colorectal cancer,, some indicate that LNY alone has no effect on survival outcome. The present study highlights that a substantial number of patients with stage I and II colorectal cancer have a low LNY.…”
Section: Discussionmentioning
confidence: 58%
“…The prognostic significance of low LNY (less than 12) is debatable in locally advanced rectal cancer treated with neoadjuvant therapy, as LNY is known to be reduced in this setting. Several studies have found no survival difference between low and high LNY groups in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was described in other solid tumor primaries, including gastric, bladder, and colorectal cancers, where more extensive lymph node dissection (LND) improves CSM . As a consequence, lymph node count targets at LND represent a quality of care indicator in several solid primary tumors, including bladder, colorectal, and gastric cancer …”
Section: Introductionmentioning
confidence: 93%